2015
DOI: 10.1093/bja/aev209
|View full text |Cite
|
Sign up to set email alerts
|

End of life decision planning in the perioperative setting: the elephant in the room?

Abstract: What previous generations called 'the art of dying' is undergoing a renaissance as an important aspect of healthcare delivery. In his recently published book, 'Being Mortal', 1 and accompanying Reith lectures, surgeon and author Atul Gawande has turned

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…15 High-quality ACP discussions will place the patient at the center of the decision-making process and help increase concordance between a patient's wishes and that of their treating team and family. 15,16 NFR Orders in the Perioperative Period Cardiopulmonary resuscitation aims to maintain cerebral and cardiac oxygenation and perfusion after a cardiac arrest and is generally administered without consent, providing all individuals with an opportunity for survival. 17 With an immediate return to circulation, the survival rate is good, but overall, the success rate remains low.…”
Section: Perioperative Advance Care Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…15 High-quality ACP discussions will place the patient at the center of the decision-making process and help increase concordance between a patient's wishes and that of their treating team and family. 15,16 NFR Orders in the Perioperative Period Cardiopulmonary resuscitation aims to maintain cerebral and cardiac oxygenation and perfusion after a cardiac arrest and is generally administered without consent, providing all individuals with an opportunity for survival. 17 With an immediate return to circulation, the survival rate is good, but overall, the success rate remains low.…”
Section: Perioperative Advance Care Planningmentioning
confidence: 99%
“…15,17 CPR can result in incredible suffering through the extension of the dying process and was a reason for the introduction of NFR orders. One study showed that allowing such instructions led to 80% of patients dying in hospital with an NFR order in place, 16 avoiding futility through the obligation to resuscitate older or terminally ill patients and allowing them a natural death.…”
Section: Perioperative Advance Care Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative assessment clinic offers a timely opportunity to ensure consent is indeed informed. In addition, this window provides an opportunity to discuss end of life wishes, establishing an advance care plan (ACP) while capacity is intact (Blackwood et al 2015 ).…”
Section: Main Textmentioning
confidence: 99%
“…13 Given an ageing population 14 with an increasing number of co-morbidities 15 and rising levels of surgery in patients who would previously have been thought not suitable, 16 it is probable that the number of high-risk patients undergoing surgery will increase in the future. In 2015, we published an editorial 17 arguing that, given the persistence of this high-risk surgical population, it would be valuable to utilise perioperative encounters to begin the process of a voluntary patient discussion documenting a patient's hopes and aspirations for the planned treatment ahead, including, where appropriate, EOL care via ACP.…”
mentioning
confidence: 99%